Aplikasi Presensi Kehadiran Online pada Karyawan PT. Bringin Karya Sejahtera dengan Metode Location-Based Service Menggunakan Android Studio dan MySQL - Dinol Panjar Asmara; NM Faizah; Maspul Aini Kambry (Design Journal, 2023)
Absence is one important performance appraisal. Absences made by each worker can affect the net monthly salary PT Bringin Karya Sejahtera is a service provider engaged in the business sector or providing services for building cleaning workers, building and building technicians. But there are some problems in his absence in the field of cleaning ATMs. Employees must come to the ATM and take selfies to take attendance. The purpose of this study is to map locations where ATM officers are located so that employees can take attendance at BRI branch offices using GPS technology, and barcodes on Android by calculating the distance to the location using the Haversine Formula method. This study also discusses absence from work due to leave, permission, sickness and overtime calculation. The development method used in designing android-based attendance applications is Rapid Application Development (RAD). The system design uses the Unified Modeling Language (UML). System coding is done using Java, PHP and MYSQL. The results of this study are the design of an android-based attendance application for employees to attend attendance at BRI branch offices.